Insuperable Language Inequalities? A Reflecting Study on Bernstein's Linguistic Codes Theory and its Critique - Biró, Barbara; Ceglédi , Tímea (Central European Journal of Educational Research, 2025)
Kindergarten education is compulsory in Hungary, and the National Basic Programme for Kindergarten Education foresees effective language activities. This is in line with what Bernstein has proposed to address language inequalities. The research question is whether linguistic differences can be observed among kindergarten students in Hungary based on the socio-economic situation of the place of residence. The investigated settlement categories according to Government Decree 105/2015. (IV. 23.), and the Central Statistical Office data were the following: disadvantaged, less disadvantaged and advantaged (N=39). The speech of kindergarteners was examined using three playful tests, which were analyzed applying dimensions and indicators determined by reviewing the literature written by Bernstein, his followers, and critics, and a pilot study. During the analysis, the underperformance of the disadvantaged settlement’s children was detected in several scales, sometimes spectacularly (adjectives, word count, sentence coherence in the first test, noun-verb relationship), sometimes only to a lesser extent (the use of conjunctions, extended sentences, personal pronouns). Overall, the results support that Bernstein’s theory created two generations ago are still valid today: language inequalities can still be experienced in terms of the settlement disadvantages. The research draws attention to the need to increase the efficiency of mother tongue development in kindergartens.